Orientation of electron spins in hybrid ferromagnet–semiconductor nanostructures. Issue 9 (26th February 2014) - Akimov, I. A.; Korenev, V. L.; Sapega, V. F.; Langer, L.; Zaitsev, S. V.; Danilov, Yu. A.; Yakovlev, D. R.; Bayer, M.; König, Jürgen; Oestreich, Michael
<x xml:space="preserve">Abstract</x> The spin orientation of electrons is studied in ferromagnet (FM)–semiconductor (SC) hybrid structures composed of a (Ga, Mn)As ferromagnetic layer, which is placed in the direct vicinity of a non‐magnetic SC <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh177xwhmj" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(In, Ga)As</alternatives> quantum well (QW). It is shown that the polarization of carriers in the SC QW is achieved by spin‐dependent tunnelling into the magnetized ferromagnetic layer. This leads to dynamical spin polarization of the electrons, which can be directly observed by means of time‐resolved photoluminescence. We find that the electron spin polarization grows in time after excitation with an optical pulse and may reach values as large as 30%. The rate of spin‐dependent capture grows exponentially steeply with decreasing thickness of the spacer between ferromagnetic layer and QW, and it persists up to the Curie temperature of the (Ga, Mn)As layer. From time‐resolved pump–probe Kerr rotation data, we evaluate a value of only a few <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh177xwh81" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μ</alternatives>eV for the energy splitting between the electron Zeeman sublevels due to interaction with the ferromagnetic (Ga, Mn)As layer, indicating that the equilibrium spin polarization is negligible. <inline-graphic xlink:href="ark:/27927/pgh177xsvqx" content-type="pssb201350236-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Schematic presentation of electron spin orientation in a semiconductor quantum well (QW) under linearly polarized excitation due to spin‐dependent capture of electrons in the ferromagnetic layer (FM). The arrows in the FM box indicate the orientation of the magnetization <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh177xwh9k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M</alternatives>. The effect is detected by appearance of a circular polarization degree of photoluminescence after pulsed optical excitation (right). The data are shown for a spacer thickness of 5 nm.